Towards integrating construction risk management and stakeholder management: A systematic literature review and future research agendas - Xia, N.; Zou, P.; Griffin, Mark; Wang, X.; Zhong, R. (Pergamon, 2018)
© 2018 We propose that integrated management of construction risk and stakeholder is feasible and can promote the effectiveness of both risk management (RM) and stakeholder management (SM). A systematic literature review is conducted on the current construction literature involving both RM and SM, through which we identify four linkage modes between risk and stakeholder management. We further suggest future directions that enable integrating risk and stakeholder management to benefit the management process and/or management outcome of RM and SM. These linkages and directions shed light on enhancing the effectiveness of RM and SM through new ways of thinking about, analyzing, and then managing risks and stakeholders in a holistic and integrated way, but not the traditional endeavor in individual areas. Integrating risk and stakeholder management is challenging, but can be a novel way for improving project performance for which this research conceptually justifies its feasibility and benefits, which merits further study.